How Tax Credits Can Support Formerly Incarcerated Individuals and Their Families. Issue 1 (May 2022) - Smith, Natalie
Tax credits like the Earned Income Tax Credit (EITC) can provide vital income support to people returning to their communities following incarceration. But the current design of the EITC prevents many from accessing the income support that it provides. In this article, I propose expanding the EITC so that it better serves communities that have been harmed by punitive criminal legal policy. An expanded EITC could raise the incomes of community members returning from incarceration by 8 to 40 percent and raise the incomes of some caregiving families by 20 to 35 percent. I also consider the potential of the Work Opportunity Tax Credit (WOTC) to encourage employers to hire justice-involved workers. Finally, I argue that policy-makers should develop a bolder, refundable tax credit targeted at individuals who return to their communities from a variety of institutions, including carceral facilities. With more inclusive tax credits, social policy can begin to redress the harms of mass incarceration and support a vision of public safety that is centered on flourishing communities.